Turkish validity and reliability of the sexual complaints screener for men. Issue 4 (2nd October 2019) - Gündüz, Anıl; Sertçelik, Sencan; Gündoğmuş, İbrahim; Zengin Eroğlu, Meliha; Kumru Bayazit, Rayka; Gönül, Hatice; Yaşar, Alişan Burak; Sungur, Mehmet Zihni
ABSTRACT: OBJECTIVE: To evaluate the validity and reliability parameters of the Turkish version of the Sexual Complaints Screener for Men (SCS-M) which is a promising brief measure to assess sexual problems in daily practice. METHODS: A cross-sectional study was conducted online. Data was collected through an online validated and content specific questionnaire via self-reporting. In total, 230 male participants between the ages of 18 and 25 submitted the questionnaire. SCS-M was translated into Turkish and applied with the International Index of Erectile Function, the Short Form Health Survey (SF-36). The p-value was evaluated statistically significant at p  < 0.05. RESULTS: The average age of participants was 21.89 ± 2.08. The Cronbach alpha internal consistency coefficient of the scale was 0.818. Correlation analysis between SCS-M, IIEF and IIEF sub-scales were statistically significant. CONCLUSION: Turkish version of the SCS-M presented good psychometric parameters. SCS-M is a valid and reliable measure for the screening and evaluation of sexual complaints. It was additionally identified as a valuable contributor to the short measures in assessing male sexual problems in research and clinical practice.